Shell Form Variation of a Freshwater Mussel Velesunio ambiguus Philippi from the Ross River, Australia - TRI HERU WIDARTO (Bogor Agricultural University, Indonesia, 2007)
Based on mussels collected from the Ross River, Australia, within 13 months, I studied the variation of their shell forms since the Ross River has changed from a flowing-water to a relatively still-water. At least four different shell forms were found including shells with characters of flowing-water species. Young mussels had distinctive Ã¢â‚¬Å“wingsÃ¢â‚¬Â at dorso-posterior part of the shells and in most cases, as the shells grew bigger, the wing development was less obvious. No significant differences were observed in obesity and relative height among mussels living in three different microhabitats (i.e. solid mud and plant litter, soft silt, soft silt and sand). The shells from Mt. Margaret Dam (a temporary dam) were thinner and their growth lines were easier to discriminate than those from the Ross River. Comparing with those living in temperate regions of Australia, the obesity and the relative height of mussels from the Ross River were smaller. Only few abnormal shells were found which usually appeared only as external deformations, such as: a light deflection on ventral margin and scars on the surface of shells. Seven age classes were found ranging between 6 and 12 years and it was estimated that the lifespan of the mussel in the Ross River was about 15 years. Key words: Velesunio ambiguus, variation, mussel, tropical water, obesity, relative height